TA Treatment of Depression: A Hermeneutic Single-Case Efficacy Design Study - ‘Anna’ - Enrico Benelli (International Journal of Transactional Analysis Research, 2017)
This study is the first of a series of seven, and belongs to the second Italian systematic replication of findings from two previous series (Widdowson 2012a, 2012b, 2012c, 2013; Benelli, 2016a, 2016b, 2016c) that investigated the effectiveness of a manualised transactional analysis treatment for depression through Hermeneutic Single-Case Efficacy Design (HSCED). The therapist was a white Italian woman with 8 years of clinical experience and the client, Anna, was a 33-year old white Italian woman who attended 16 sessions of transactional analysis psychotherapy. Anna satisfied DSM-5 criteria for mild persistent depressive disorder (dysthymia) with anxious distress. The conclusion of the judges was that this was a good-outcome case: the dysthymic symptoms improved over the course of the therapy and were maintained in the ‘healthy’ range at the 6-month follow-up, the client reported a positive experience of the therapy and described important changes in intrapsychic and interpersonal patterns. In this case study, transactional analysis treatment for depression has proven its efficacy in treating persistent depressive disorder.